2021
DOI: 10.1186/s12887-021-03001-7
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, clinical, and socioeconomic factors associated with delayed diagnosis and management of pediatric testicular torsion in West China: a retrospective study of 301 cases in a single tertiary children’s hospital

Abstract: Background To investigate the association between geographic, clinical, socioeconomic factors and delayed management of pediatric testicular torsion (TT) in West China. Methods A retrospective study was conducted on TT at Children’s Hospital of Chongqing Medical University in West China from November 2004 to December 2020. Univariate analysis and logistic regression analysis were conducted to determine the association between these factors and dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
2
7
0
Order By: Relevance
“…Regarding socioeconomics, children living in low economic areas and not close to a medical center had a higher risk of delayed surgery, consistent with previous findings of delayed surgery for cryptorchidism and testicular torsion [ 22 , 23 ]. Newborns with hypospadias are generally examined and given preliminary treatment advice by the primary community physicians.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding socioeconomics, children living in low economic areas and not close to a medical center had a higher risk of delayed surgery, consistent with previous findings of delayed surgery for cryptorchidism and testicular torsion [ 22 , 23 ]. Newborns with hypospadias are generally examined and given preliminary treatment advice by the primary community physicians.…”
Section: Discussionsupporting
confidence: 88%
“…Regarding socioeconomics, children living in low economic areas and not close to leading medical centers had a higher risk of delayed surgery, consistent with previous ndings of delayed surgery for cryptorchidism and testicular torsion [22,23]. Newborns with hypospadias are generally examined and given preliminary treatment advice by the primary community physicians.…”
Section: Discussionsupporting
confidence: 78%
“…We found a correlation between age and TS, with younger children being more likely to undergo orchiectomy. This may be because younger children are unable to judge the severity of pain and accurately describe pain symptoms in words[ 17 ]. Similarly, Bayne et al [ 18 ] reported that misdiagnosed patients tended to be younger and more likely to have developmental, cognitive, or social disorders than those in an acute setting[ 18 ].…”
Section: Discussionmentioning
confidence: 99%